2021
DOI: 10.1038/s41467-021-25274-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined intermittent fasting and ERK inhibition enhance the anti-tumor effects of chemotherapy via the GSK3β-SIRT7 axis

Abstract: Dietary interventions such as intermittent fasting (IF) have emerged as an attractive strategy for cancer therapies; therefore, understanding the underlying molecular mechanisms is pivotal. Here, we find SIRT7 decline markedly attenuates the anti-tumor effect of IF. Mechanistically, AMP-activated protein kinase (AMPK) phosphorylating SIRT7 at T263 triggers further phosphorylation at T255/S259 by glycogen synthase kinase 3β (GSK3β), which stabilizes SIRT7 by decoupling E3 ligase UBR5. SIRT7 hyperphosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Next, we aimed to identify the factor(s) regulating de novo Akt-dependent lipid synthesis in PAH. Several studies demonstrate that lysine deacetylase SIRT7 coordinates cellular metabolic balance by regulating glucose sensing/homeostasis, glycolysis, mitochondria and ribosomal biogenesis, DNA damage response, fatty acid synthesis and overall lipid metabolism ( 50 56 ). Moreover, it was recently shown that SIRT7 modulates aortic vascular smooth muscle cell proliferation in wire injury model of the femoral artery ( 57 ) and promotes cancer progression by activating Akt ( 56 , 58 ) and mTORC1 effector S6K1 ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we aimed to identify the factor(s) regulating de novo Akt-dependent lipid synthesis in PAH. Several studies demonstrate that lysine deacetylase SIRT7 coordinates cellular metabolic balance by regulating glucose sensing/homeostasis, glycolysis, mitochondria and ribosomal biogenesis, DNA damage response, fatty acid synthesis and overall lipid metabolism ( 50 56 ). Moreover, it was recently shown that SIRT7 modulates aortic vascular smooth muscle cell proliferation in wire injury model of the femoral artery ( 57 ) and promotes cancer progression by activating Akt ( 56 , 58 ) and mTORC1 effector S6K1 ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrate that lysine deacetylase SIRT7 coordinates cellular metabolic balance by regulating glucose sensing/homeostasis, glycolysis, mitochondria and ribosomal biogenesis, DNA damage response, fatty acid synthesis and overall lipid metabolism (50)(51)(52)(53)(54)(55)(56). Moreover, it was recently shown that SIRT7 modulates aortic vascular smooth muscle cell proliferation in wire injury model of the femoral artery (57) and promotes cancer progression by activating Akt (56,58) and mTORC1 effector S6K1 (59). We found that SIRT7 protein levels were significantly higher in human PAH PAVSMC compared to non-diseased PAVSMC (Figures 4A,B).…”
Section: Sirt7 Up-regulates Akt and Lipogenic Enzymes In Human Pah Pa...mentioning
confidence: 99%
“…In KRAS mutant PDAC, autophagy promotes tumor growth, synergistically inhibiting insulin-like growth factor 1 receptor (IGF1R), and ERK1/2 increases the sensitivity to autophagic inhibitors . Interestingly, intermittent fasting, a potentially promising dietary intervention strategy in cancer therapy, combined with ERK1/2 inhibition can effectively enhance the efficacy of chemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…76 Interestingly, intermittent fasting, a potentially promising dietary intervention strategy in cancer therapy, combined with ERK1/2 inhibition can effectively enhance the efficacy of chemotherapy. 77 In summary, ERK1/2 will be expected to become a promising druggable target to greatly improve potential cancer therapy after RAS, RAF, and MEK. With the continuous design of ERK1/2 inhibitors according to different strategies and a better understanding of their clinical trials, we believe that these inspiring findings will shed new light on the discovery of more specific and potent inhibitors of ERK1/2 as candidate small-molecule drugs for future cancer therapeutics.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…Despite the oncogenic effects of SIRT7, the high levels of this protein in breast cancer cells make them susceptible to the effects of fasting, where SIRT7 is phosphorylated at residue T263 by AMPK and then at residue S259 by GSK3β to prevent its binding to E3 ligase UBR5 and subsequent polyubiquitination and degradation. Hyperphosphorylated SIRT7 can bind to and stabilize SKP2, preventing its EGF-induced protein turnover and subsequently compromising AKT activation [ 132 ].…”
Section: Aging-associated Diseasesmentioning
confidence: 99%